IgG1 and IgG4 antibodies against Core and NS3 antigens of hepatitis C virus - Vanessa Costa dos Santos; Maria Isabel Schinoni; Isabela Silva de Oliveira; Maria Luiza Sousa Atta; Ajax Mercês Atta (Revista da Sociedade Brasileira de Medicina Tropical, 2019)
Abstract INTRODUCTION: IgG subclasses involved in the immune response to hepatitis C virus (HCV) antigens have been rarely studied. We investigated the immune response mediated by IgG1 and IgG4 antibodies against the recombinant core and NS3 antigens in patients with chronic hepatitis C. METHODS: Sixty patients infected with HCV genotype 1 without antiviral treatment and 60 healthy subjects participated in the study. Serum levels of alanine aminotransferase, HCV viremia, and the presence of cryoglobulinemia and liver fibrosis were determined. We investigated the serum IgG1 and IgG4 antibodies against recombinant HCV core and NS3 non-structural protein antigens using amplified indirect ELISA. RESULTS: Anti-core and anti-NS3 IgG1 antibodies were detected in 33/60 (55%) and 46/60 (77%) patients, respectively, whereas only two healthy control samples reacted with an antigen (NS3). Anti-core IgG4 antibodies were not detected in either group, while 30/60 (50%) patients had anti-NS3 IgG4 antibodies. Even though there were higher levels of anti-NS3 IgG4 antibodies in patients with low viremia (< 8 × 105 IU/mL), IgG1 and IgG4 antibody levels did not correlate with ALT levels, the presence of cryoglobulinemia, or degree of hepatic fibrosis. High production of anti-core and anti-NS3 IgG1 antibodies was observed in chronic hepatitis C patients. In contrast, IgG4 antibodies seemed to only be produced against the NS3 non-structural antigen and appeared to be involved in viremia control. CONCLUSIONS: IgG1 antibodies against structural and non-structural antigens can be detected in chronic hepatitis C, while IgG4 antibodies seem to be selectively stimulated by non-structural HCV proteins, such as the NS3 antigen.